Gender Equality From Ra. Kartini’s Perspective and Its Relevance in Education - Nur Rohmah Nilam Sari; Neni Mariana; Heru Subrata (South Sulawesi Education Development (SSED), 2024)
The purpose of this article is to examine the concept of gender equality in education which was echoed by Kartini during colonialism. This study found that there was relevance of the concept of gender equality at that time in the education system. Apart from that, this article also reveals how Kartini's thoughts can influence education, especially focusing on gender access, analyzes several forms of discrimination based on gender regarding educational rights during colonialism which had an impact on education policy, and analyzes the follow-up actions that must be taken in efforts to overcome gender equality. in education. It begins with an analysis of the concept of gender equality in the global concept that occurred during colonialism which is drawn into Kartini's local concept of gender equality in education. Thus, we can get a gender policy concept that can be generalized in the world of education.